Study Of Cu-Doped Zno Films Deposited On Different Substrates Using Magnetron Sputtering - Yusof, Ahmad Sauffi (2019)
Zinc oxide (ZnO) thin films have emerged as an interesting research area owing to its useful properties. Recently, lots of attention have been given to doped ZnO films with copper (Cu) atom, due to its favourable potential in semiconductor devices. This work was focused on the un-doped and Cu-doped ZnO (CZO) thin films prepared by reactive magnetron sputtering. Different sputtering parameters were introduced to improve the properties of the films mainly by manipulating the Cu content and the type of substrate. The crystal structure, optical properties, surface morphology and electrical properties were investigated by using X-ray diffraction (XRD), ultraviolet-visible (UV-VIS) spectrophotometer, field emission scanning electron microscopy (FE-SEM), atomic force microscopy (AFM) and Hall effect measurement with a four-point Van der Pauw configuration. ZnO and CZO films were deposited on the glass, p-GaN/Al2O3 and n-GaN/Al2O3 substrates using radio frequency magnetron sputtering of ZnO (10wt% Cu doped) target at 200o C. XRD results indicated that ZnO and CZO films with preferential orientation along c-axis that belongs to a hexagonal wurtzite structure were fabricated. The transmittance of all ZnO and CZO films deposited on the glass substrate were more than 85% in the visible region. Optical band gap reduction was observed when Cu introduced into ZnO structure. Deposited CZO films showed a smoother surface as compared to ZnO films.